2012
DOI: 10.2139/ssrn.1993172
|View full text |Cite
|
Sign up to set email alerts
|

Do Investors Value Cash Flow Stability of Listed Infrastructure Funds?

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…As far back as two decades ago, Sanchez-Robles (1998) pointed out that infrastructure investment has a positive and significant relationship with a country's GDP. It has also been shown that FDII rises during economic downturns (Bitsch, 2012), and this was confirmed during the Asian financial crisis of 1998 as well as in the global financial crisis of 2008. Contrary to the predictions of Ramamurti and Doh (2004), FDII has continued to rise since.…”
Section: Foreign Investment and Political Risk 1fdi And Fdii In Devementioning
confidence: 84%
“…As far back as two decades ago, Sanchez-Robles (1998) pointed out that infrastructure investment has a positive and significant relationship with a country's GDP. It has also been shown that FDII rises during economic downturns (Bitsch, 2012), and this was confirmed during the Asian financial crisis of 1998 as well as in the global financial crisis of 2008. Contrary to the predictions of Ramamurti and Doh (2004), FDII has continued to rise since.…”
Section: Foreign Investment and Political Risk 1fdi And Fdii In Devementioning
confidence: 84%
“…For the utility, transport, and telecom companies, the average betas were 0.50, 0.73, and 1.09, respectively. 2 Bitsch (2012) finds that infrastructure vehicles are priced using a highrisk premium in part because of complex and opaque financial structuring, information asymmetries with managers, and regulatory and political risks.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In line with Huang (2009), but not in line with Bitsch (2012), who finds a positive relation between cash flow volatility and a fund's value.…”
Section: Significantly Negativementioning
confidence: 82%
“…Results about inflation are ambiguous, but it seems that no general inflation hedge is provided by infrastructure investments. Cash flow volatility is analyzed by Bitsch (2012), who finds more stable cash flow for unlisted infrastructure deals but cannot confirm a premium for such stability.…”
Section: Introductionmentioning
confidence: 97%